The use of metabolic power to assess physical demands in soccer: how does it differ from the traditional approach through speed running? - Martinez-Cabrera, F. I.; Nunez-Sanchez, F. J. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Metabolic power and speed running are in the top-10-ranked variables used to quantify the physical demand in soccer matches or training practices. The main purpose of this study was to compare metabolic power (MP) and the traditional approach using speed running during soccer matches in absolute values and in zones of intensity in function of the playing positions. METHODS: Thirty-eight professional soccer players were analyzed during 18 friendly matches from 4 preseasons (N.=300) and divided into 5 groups of playing positions: central defender (CD) (N.=64), wide defender (WD) (N.=55), central midfielder (CM) (N.=58), wide attacker (WA) (N.=70), and attacker (AT) (N.=53). The individual profiles to each playing positions were assessed using MP and speed running approaches. The magnitude of change was substantial when there was a =75% likelihood of the effect. The effect size was also calculated using a confidence interval of 90%. RESULTS: In absolute values, CMs and WAs had substantially greater values than did the other positions, with CMs having the highest values in both approaches and an identical relationship between the positions in both approaches. In categories of intensity, medium-low intensity displayed differences between the approaches; the physical demands of ATs and CDs were lower using the traditional approach but were higher than the other playing positions when assessed using MP. No differences were found at low, medium or high intensities. CONCLUSIONS: The MP and energy expenditure reported differences at medium-low intensity compared to the speed running traditional approach between playing positions. However, the other intensities did not report differences compared to the traditional approach in the different playing positions.